Hi.

I’m stuck on the second part of this polynomial question.

I’ve got the first part:

- A is 2

- B is 1

- C is 2

How do I go about solving the second part of this question:

Thanks in advance,

bqrs01

bqrs01 May 14, 2019

#1**+3 **

The graph "kisses" the x axis at x = 1 and goes through the x axis at x = -2

Therefore....we have that

y = (x + 2) (x - 1)^2

When x = 0, then "c" = 2

So....we have that

( x + 2)(x-1)^2 = 2

(x + 2) ( x^2 - 2x + 1) = 2

x^3 +2x^2 -2x^2 -4x + x+ 2 = 2

x^3 - 3x = 0

x( x^2 - 3) = 0 set both factors to 0 and solve for x

x = 0 and x^2 - 3 = 0 ⇒ x^2 = 3 ⇒ x = ± √3

Here's a graph : https://www.desmos.com/calculator/co5bdggyfq

CPhill May 14, 2019